ДИНИЙ-ТАСАВВУФИЙ АДАБИЁТ ВА ОЛИМ ШАРАФИДДИНОВ ҚАРАШЛАРИ - Атаниязова, М. (SCIENCE and SOCIETY, 2021)
This article analyzes the views of Olim Sharafiddinov on religious Sufi literature and some of its representatives. It reveals the problems associated with the study of the works of creators such as Ahmad Yassaviy, Suleyman Bokirgoni, Rabguzi. At the same time, attention is paid to the problems of today’s literary criticism.